Creación de un trámite agil para la suspensión de la patria potestad - Cantos Lopez, Carmita Jeanneth (2014)
This thesis is in its most practical sense, an analysis naturally focused on a very stark reality that occurs within the scope of "CREATING AN AGILE PROCESS FOR SUSPENSION OF PARENTAL RIGHTS." In this situation, the Code on Children and Adolescents suspension of parental rights it should be done following the litigation process generally, a procedure that is unduly prolonged, it has three levels, as also may file an appeal of so that it is often impossible to request the suspension of parental authority, therefore, my proposal that the suspension of parental authority has a streamlined process for the interests of the child can be ensured. Thus my thesis research relates to this issue that certainly generates legal uncertainty, so it became necessary to introduce doctrinal, conceptual and legal sources that allowed me to address the legal institution of the suspension of parental rights and analyze the Code of Children and Adolescents as a new branch of law that is taking autonomy in the future development of society and law. In the research I was useful criterion investigated population coincided with my view that it is necessary to reform the Code of Children and Adolescents incorporating my proposal that the suspension of parental authority has an agile process to be guaranteed the best interests the child. In this context, this thesis is a reference that invites us to reflect on the best interests of the child in Ecuador and studies necessary for the full development of society. My thesis and thus refers to the need for reform and indicated is based on theoretical and practical convenience of reform that I formulated my final conclusion of investigation.